Dr. Gaanty Pragas receives award from IKM - M. M., Yusoff; Saifful Kamaluddin, Muzakir; Chin, Mei Lee; Siti Aisah, Harun; Norhayati, Nordin; Ezrinda, Mohd Zahidee; Mohd Fazli, Farida Asras; Nurul Nadia, Abd Razak (Penerbit UMP, 2011)
DEC 9, KUALA LUMPUR : The Tan Sri Datuk Ong Kee Hui Postgraduate Chemistry Medal is given annually to the most outstanding chemistry postgraduate thesis by lnstitut Kimia Malaysia (IKM) since 1974.